A Literature Review on Digital Marketing Strategies and Its Impact on Online Business Sellers During the COVID-19 Crisis - Alreany C. Tabuena; Shiella Mae L. Necio; Kyle Kirsten Macaspac; Maria Paula E. Bernardo; Dominic I. Domingo; Princess Daryl M. De Leon (Cita Konsultindo Research Center, 2022)
The primary objective of this literature review is to examine the digital marketing strategies used by online business sellers amidst the COVID-19 pandemic. In this case, effective marketing enables the collection of data to understand more about the targeted consumers, allowing advertising and other strategies to be more directed. In addition, this was initiated to deeply understand how the digital marketing strategies of online business sellers work. Based on the literature review, the researchers identified the following themes: digitalization and digital marketing, digital and traditional modes of marketing, social media as a digital marketing strategy, information technologies as marketing tactics, e-commerce during the COVID-19 pandemic, understanding online, internet, mobile, and digital marketing, preferences, and future research directions, and implications. In conclusion, digital marketing has surpassed traditional marketing. These elements affect the digital marketing skills gap. Internet ads are getting more widespread. Firms' perceptions of the value of digital marketing can be classified. An integrated approach is required to meet client needs using digital marketing channels. To succeed in this new market, businesses must first understand their clients' lifestyles. Digital marketing has evolved into an internet advertising platform for small business owners, despite a lack of funds to update technology and harness internet development. Advertising on social media is attracting the attention of digital marketers. Because of the potential market share gains that social media marketing could give for internet marketers, it is expected that social advertising spending will continue to grow in the coming years